Josef Dobrovský a jeho přínos k výzkumu literárních rukopisů - Petr, Stanislav (Masarykův ústav + Archiv, Na Florenci 3, Praha 1, http://www.mua.cas.cz, 2004)
The contribution follows Dobrovský’s research of manuscripts from the beginnings in 1780s till his death in 1829. His pioneer work at the research of manuscript bohemica abroad is described in details. The author attempts to identify Dobrovský’s finds of manuscripts and completes its present deposition. He follows Dobrovský’s research of the Czech manuscripts of Bibles and other literary manuscripts, and evaluates the contribution of his work for present research.
Keywords: rukopisy; manuscripts; slavistika; Slavonic studies